Peran Apolipoprotein B, Apolipoprotein A, dan Rasio ApoA/ApoB sebagai Prediktor Terjadinya Demensia pada Kelompok Lanjut Usia - Sim, Alfred Sutrisno; Santoso, Alexander Halim; Gunaidi, Farell Christian; Alifia, Khalisya; Aditya, Vincent; Destra, Edwin (Pusat riset dan Inovasi Nasional, 2025)
Neurocognitive disorders, particularly dementia, affect various cognitive functions such as memory, attention, language, learning, and problem-solving, with the elderly population being the most impacted. The prevalence of dementia is projected to rise to 131 million cases by 2050, posing significant social and economic implications. This study employed a cross-sectional method to evaluate the role of Apolipoprotein A (APOA) and Apolipoprotein B (APOB) in the diagnosis and prevention of dementia in older adults. The results showed that Apolipoprotein A was not significantly correlated with MMSE scores, indicating no clear relationship between APOA and cognitive function. In contrast, Apolipoprotein B demonstrated a significant negative correlation with MMSE, suggesting that increased APOB levels are associated with cognitive decline. Elevated ApoB, linked to increased LDL and oxidative stress, correlated with reduced cognitive function, whereas ApoA, the main component of HDL, is associated with neuroprotective effects. These findings underscore the importance of monitoring lipid profiles, including ApoA and ApoB, in the prevention and management of dementia in the elderly.